The Effect of Financial and Non-Financial Compensation on the Performance of Frontline Employees with Intrinsic Motivation as a Mediating Variable : (A Study at PT. Bank Rakyat Indonesia (Persero) Tbk. KC Palangka Raya) (International Journal of Economics and Management Research, 2026)
This study aims to analyze the effect of financial and non-financial compensation on frontliner employee performance with intrinsic motivation as a mediating variable at PT Bank Rakyat Indonesia (Persero) Tbk Palangka Raya Branch Office). This study aims to analyze the influence of financial and non-financial compensation on frontliner employee performance with intrinsic motivation as a mediating variable at PT Bank Rakyat Indonesia (Persero) Tbk, Palangka Raya Branch Office. The research employs a quantitative approach using 67 respondents and data analysis with Structural Equation Modeling (SEM-PLS). The results show that both financial and non-financial compensation have a positive and significant effect on employee performance and intrinsic motivation. Furthermore, intrinsic motivation significantly affects performance and mediates the relationship between compensation and performance. The R² value of 0.681 indicates that the model explains 68.1% of performance variation. These findings reinforce Herzberg’s Two-Factor Theory and Self-Determination Theory, emphasizing the importance of balancing material and non-material compensation to enhance motivation and sustainable performance among frontliner employees in the banking sector.